2016
DOI: 10.1111/pedi.12476
|View full text |Cite
|
Sign up to set email alerts
|

Low perinatal zinc status is not associated with the risk of type 1 diabetes in children

Abstract: The risk of developing T1D in Danish children was not associated with perinatal zinc status nor age at onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our start of follow-up was 18 months, in the offspring analyses, excluding children diagnosed before this age (1.56%) and no change in results were seen when follow-up was postponed one year (30 months of age); (viii) potential micronutrient-micronutrient interactions regarding association with childhood T1D could not be well-examined in this study. Though, there is no strong evidence in the literature that iron supplementation would e.g., affect zinc status negatively or vice versa or that low zinc status could increase risk of T1D [44,45,46]; and (ix) our results may be influenced by residual confounding.…”
Section: Discussionmentioning
confidence: 79%
“…Our start of follow-up was 18 months, in the offspring analyses, excluding children diagnosed before this age (1.56%) and no change in results were seen when follow-up was postponed one year (30 months of age); (viii) potential micronutrient-micronutrient interactions regarding association with childhood T1D could not be well-examined in this study. Though, there is no strong evidence in the literature that iron supplementation would e.g., affect zinc status negatively or vice versa or that low zinc status could increase risk of T1D [44,45,46]; and (ix) our results may be influenced by residual confounding.…”
Section: Discussionmentioning
confidence: 79%
“…It has also been found that high iron concentrations at birth is associated with an increased risk of T1D [3]. Deficiency of zinc, a central part of the insulin hexamer, is regarded to be related to increased risk of diabetes and there are also epidemiological studies supporting a role for low zinc in the risk for T1D [4] while low perinatal zinc status was not associated with the risk of T1D later in children [5]. However, metals that have no physiological role in the human physiology but should rather be regarded as toxic, may play a role.…”
Section: Introductionmentioning
confidence: 99%
“…The use of NBS in diabetes research to date may be summarized as follows: risk prediction for type 1 diabetes development, determining metabolic perturbations in infants exposed to maternal diabetes, confirming the metabolite signature of a recently discovered monogenic diabetes gene and determining the feasibility of testing neonatal diabetes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. These studies utilized either pre-existing results, reused and reanalyzed DBS (using the card as a biobank) for new biomarkers or a combination of both.…”
Section: Available Literature On Diabetes and Newborn Screeningmentioning
confidence: 99%
“…The second study reported a reanalysis of dried blood spots to test glucose levels for neonatal diabetes and established median capillary glucose levels for neonatal diabetes (cases vs. matched controls: 18.7 (10.2 to >30.0) vs. 4.6 (2.3–6.2) mmol/L, p ≤ 0.001), demonstrating that newborn screening for neonatal diabetes was feasible [ 1 , 24 ]. Two studies showed no associations between vitamin D [ 25 , 26 ] or zinc concentrations [ 27 ] and type 1 diabetes development.…”
Section: Available Literature On Diabetes and Newborn Screeningmentioning
confidence: 99%